Mutual effect of extrinsic defects and electronic carbon traps of M-TiO2 (M = V, Co, Ni) nanorod arrays on photoexcited charge extraction of CdS for superior photoelectrochemical activity of hydrogen production. (2nd August 2018) - Mumtaz, Asad; Mohamed, Norani Muti; Irshad, Muhammad Imran; Yar, Asfand; Mohamed Saheed, Mohamed Shuaib
Abstract: Understanding the photoexcited charge carrier dynamics such as separation, transportation and extraction in smart hybrid nanocomposites is the key to high performance solar cells. Nanocomposites possess advantage of broader solar absorption with their fast photoexcited charge separation and transportation but their use as photocorrosion-stable material is yet to be explored. Also, bulk and surface defects in individual components of the nanocomposites boost the efficiency of the solar cells, despite of the fact the recombination of the photoexcited charges at the interfaces lead to a substantial loss of charges and realizing a big challenge. Herein, the extrinsic defects like bulk and surface defects are induced by transition metal (M = V, Co, Ni) doping of M − TiO2 nanorod arrays. Consequently, the hydrothermal synthesis method offers the tuning of the carbon trapping states depending upon the type of the metal doped in M − TiO2 that decelerates the charge carrier dynamics in the M-TiO2 /CdS (M = V, Co, Ni) nanocomposites with the increase in the amount of carbon. Excellent charge extraction is observed in VTiO2 (4% carbon) from its CdS sensitizer with photocurrent density of 2.06 mA/cm 2 than NiTiO2 (14.6% carbon), TiO2 (18.94% carbon) and CoTiO2 (39.2% carbon) with photocurrent densities of 1.83, 1.46 and 1.34 mA/cm 2 at 0 V versus Ag/AgCl under 100 mW/cm 2 light intensity, respectively. This shows primary dependence of photoexcited charge dynamics upon the density of the carbon trapping states to be least while secondary dependence upon the density of the extrinsic defects in M − TiO2 to be maximum. This work creates a paradigm for future studies to have a broader insight of the photocatalyst's overall functioning to boost the efficiencies in solar cells by controlling the amount of electronic carbon traps during the synthesis of a large class of inorganic semiconductor photocatalysts. Graphical abstract: Image 1 Raman spectra of M − TiO2 nanorod arrays are showing the increasing trends of electronic carbon traps (black arrow) and extrinsic defects (green arrow). While, photocurrent density and voltage plot of transition metal doped M-TiO2 /CdS (M = V, Co, Ni) show its primary dependence upon amount of carbon content in M − TiO2 determined through Raman spectroscopy and secondary dependence upon its extrinsic defects i.e., oxygen vacancies, mid gap energy states. The primary dependence is indirect i.e., higher the amount of carbon content in transition metal (TM) doped M − TiO2, thus lower is the output photocurrent density in the corresponding heterojunction bilayer. Highlights: Transition metals (TMs) doped M–TiO2 /CdS (M = V, Co, Ni) heterojunctions are established. TMs doping of TiO2 nanorod arrays introduce extrinsic (bulk and surface) defects and electronic carbon traps (ECTs). V, as compared to Co and Ni doping of TiO2 nanorod arrays, eliminates ECTs. VTiO2 /CdS heterojunction exhibits the highest photoelectrochemical activity for hydrogen production. Least density of ECTs and optimum density of extrinsic defects increase the overall charge carrier dynamics in photocatalysis.